Motivasi Belajar PJOK Melalui Pembelajaran Daring Pada Peserta Didik Kelas X SMA Negeri 1 Blahbatuh Gianyar Tahun Pelajaran 2020/2021 - Dewi, Ni Kadek Sri Kesuma; Darmayasa, I Putu; Wijaya, Made Agus (Faculty of Sport and Health Sciences, 2021)
This study aims to determine the learning motivation of PJOK through online learning from class X students of SMA Negeri 1 Blahbatuh Gianyar. This type of research is descriptive quantitative research with survey method. The population used in this study were students of class X SMA Negeri 1 Blahbatuh Gianyar for the academic year 2020/2021, totaling 418 students. The sample technique used was random sampling as much as 25% of the total population of 104 students. The data collection technique uses a questionnaire with google form. Data were analyzed using quantitative descriptive statistics with percentages. The results of data analysis on PJOK learning motivation through online learning in class X students of SMA Negeri 1 Blahbatuh Gianyar showed three people (2.88%) very high, 79 people (75.96%) high, 22 people (21.15%) moderate. From the results of data analysis, it was concluded that the motivation to learn PJOK through online learning in class X SMA Negeri 1 Blahbatuh Gianyar students in the high category. It is recommended for PJOK teachers to always be able to maintain or increase PJOK learning motivation through online learning in class X students of SMA Negeri 1 Blahbatuh Gianyar.